Fouling communities and non-native species within five ports along the Bristol Channel, South Wales, UK. (5th May 2021) - Holmes, Samuel; Callaway, Ruth
Abstract: Non-native species (NNS) are widely regarded to be one of the major threats to the loss of biodiversity worldwide. Maritime trade is the primary pathway for the transport and introduction of aquatic NNS around the world, and ports are central to this network. Our knowledge of port communities and the NNS they contain is limited, with ports often remaining unsurveyed for decades, which was the case within the studied region. Settlement plates were deployed for 10–11 months at five commercial ports along the Bristol Channel and Severn Estuary in South Wales, UK. We report unique communities in each of the ports with salinity being the main driver for differences among locations. Eleven NNS were identified across all ports with non-native to native species proportions ranging from 0.13 to 0.33 in each port. Most of these NNS are known to exist in the region and are 'established' species within the UK. High variation in community structure and NNS composition among all ports independent of geographic proximity highlights the importance of monitoring individual ports with a view to implementing bespoke, effective NNS management strategies. Highlights: Fouling communities were surveyed within 5 UK ports. Communities can vary significantly between ports in close proximity to one another. Eleven non-native species were identified in 5 ports. Non-native species accounted for up to one species for every three native species. Port baseline surveys are key to providing effective non-native species management.